2006
DOI: 10.1103/physrevb.73.125407
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the melting of aluminum clusters

Abstract: The melting of Al clusters in the size range 49 ≤ N ≤ 62 has been studied using two model interatomic potentials. The results for the two models are significantly different. The glue potential exhibits a smooth relatively featureless heat capacity curve for all sizes except for N = 54 and N = 55, sizes at which icosahedral structures are favoured over the polytetrahedral. Gupta heat capacity curves, instead, show a well-defined peak that is indicative of a first-order-like transition. The differences between t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 57 publications
3
45
0
Order By: Relevance
“…The nature of melting in these clusters is thus easily related to the properties of the potential energy landscape in the vicinity of the starting atomic configuration in the heating runs. Several other authors 23,25,31 have found a reduction in the latent heat as the solid and liquid structures become more similar. Calorimetric 7 and photoelectron 5 experiments reveal that a smooth ͑as oppossed to abrupt͒ melting transition should also be expected for clusters below a small critical size, which for sodium clusters seems to be around 50 atoms ͑with few exceptions͒.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The nature of melting in these clusters is thus easily related to the properties of the potential energy landscape in the vicinity of the starting atomic configuration in the heating runs. Several other authors 23,25,31 have found a reduction in the latent heat as the solid and liquid structures become more similar. Calorimetric 7 and photoelectron 5 experiments reveal that a smooth ͑as oppossed to abrupt͒ melting transition should also be expected for clusters below a small critical size, which for sodium clusters seems to be around 50 atoms ͑with few exceptions͒.…”
Section: Introductionmentioning
confidence: 90%
“…On one hand, we have so-called amorphous clusters. 19,23,25,31 As the "amorphous" attribute is presently employed in rathers loose sense when referring to clusters, it must be said that several groups consider clusters as amorphous when they show little or no discernible structural order. Aguado et al 19 first proposed that a fully amorphous cluster should possess neither angular nor radial order ͑this last requisite being frequently overlooked as angular disorder is more easily identified by visual inspection͒, but obviously shows some short-range order, mostly restricted to the first coordination shell about each atom.…”
Section: Introductionmentioning
confidence: 99%
“…The Gupta potential parameters for cesium metal are shown in Table 1 [30]. Gupta potential function has been applied to describe structure and energy of Pb [31], Ni, Ag, and Au nanoclusters [32], the Cu-Au nanoalloy clusters using a genetic algorithm [33], the melting of aluminum clusters [34], the structural patterns of unsupported gold clusters [35], and disordered global-minima structures for Zn and Cd nanoclusters [36]. Also, this potential has been used for simulation in many instant with satisfactory results.…”
Section: Potential Modelmentioning
confidence: 99%
“…However we now give an example of this superheating and the corresponding first-order transition to coexistence obtained by MD simulations of Al nanoparticles using the glue potential [25]. With this potential, closed-shell Al clusters with 586 or more atoms favor TO structures [26]. We simulated caloric curves for the 586, 1289, 2406 and 4033-atom TO clusters.…”
mentioning
confidence: 96%